2011
DOI: 10.1080/02626667.2011.580747
|View full text |Cite
|
Sign up to set email alerts
|

Water crisis: From conflict to cooperation—an overview

Abstract: The quantity of freshwater available per person in the world has been and continues to decrease due to a combination of factors, including population increase, water pollution, inadequate planning and management of transboundary and other shared waters, and inefficient operation of water supply and distribution systems. Consequently, there is an increasing potential for water scarcity, crisis and associated conflicts around the world in the future, especially in developing regions, if the current trend in wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 69 publications
0
58
0
4
Order By: Relevance
“…There is no doubt that these aspects have indeed been extensively addressed in water-related studies, in one way or another (see, for example, Shiva 2002, Iyer, 2007, Biswas et al 2009, for some details; see also Sivakumar, 2011 and the references therein). However, such studies have largely been limited to water quantity, quality and socio-economic aspects, including the applications of scientific methods such as the Delphi Technique, Expert Systems and Decision Support Systems.…”
Section: Methods For Solving the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no doubt that these aspects have indeed been extensively addressed in water-related studies, in one way or another (see, for example, Shiva 2002, Iyer, 2007, Biswas et al 2009, for some details; see also Sivakumar, 2011 and the references therein). However, such studies have largely been limited to water quantity, quality and socio-economic aspects, including the applications of scientific methods such as the Delphi Technique, Expert Systems and Decision Support Systems.…”
Section: Methods For Solving the Problemmentioning
confidence: 99%
“…Lorey 2003; see also Sivakumar, 2011, for some general details). The consequences of lack of water are being disseminated in the simplest and most blunt way, particularly for the layman to access and understand, as has been done in an article entitled "Water shortages foster terrorism" (Sutherland 2003), a report from Tokyo for BBC News, quoting the presentation by Mona El Kody, the Chair of the National Water Research Unit in Egypt, at the Third World Water Forum.…”
Section: Water and Human Psychology: Hydropsychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mei, etc. found that the biofilm technique would be more effective in purifying black-odor water with the application of sediment aeration techniques beforehand, through a laboratory experiment which showed that the removal rates of NH 4 + -N and COD reached up to 63.25% and 53.06%…”
Section: Numbermentioning
confidence: 99%
“…The remaining 97.5% is in the form of saltwater in the oceans and saline groundwater. Freshwater from lakes and rivers, acting as the main sources of human water consumption, only contains an average of about 90,000 km 3 of water and just 0.26% of the total global freshwater resources [1]. Global demand for water has increased up to three times with the surge of the population since the 1950s, while the supply of fresh water has been continuously declining [2].…”
Section: Introductionmentioning
confidence: 99%